Field experiment on the uptake of lead, strontium, cobalt, and nickel in the wood and bark of spruce (Picea abies L.) and Douglas-fir (Pseudotsuga menziesii Mirb.) - Milošević Ivana R.; Živković Sanja; Momčilović Miloš; Višnjić-Jeftić Željka; Veselinović Milorad; Marković Ivana D.; Marković Dragan M. (Journal of the Serbian Chemical Society)
Human activities have significantly altered the availability and circulation of pollutants, impacting their concentrations in the environment. This pollution notably affects trees. In this study, we conducted two separate experiments (I and II) to investigate the uptake of lead, strontium, cobalt, and nickel in spruce (Picea abies L.) and Douglas-fir (Pseudotsuga menziesii Mirb.) seedlings. These seedlings were exposed to elevated levels of these metals by adding them to the soil. Our field experiments provide insights into metal accumulation in natural environments. We measured concentrations of these elements, along with manganese and zinc, in the soil, wood, and bark using inductively coupled plasma-optical emission spectrometry (ICP-OES). The results showed increased levels of the added metals in the wood and bark of both tree species. Notably, there was a significant increase in lead and nickel concentrations in Douglas-fir wood. The lead concentration in Douglas-fir wood was 7 and 4 times higher in experiments I and II, respectively, compared to the control group of seedlings, while the nickel concentration was 18 and 10 times higher. These findings suggest that Douglas-fir wood has potential for phytostabilization of lead and nickel based on trace element concentrations and transfer factors.